Ober Funktionen, die keine nullgleiche dividierte Differenz n-ter Ordnung besitzen - Kirjatsky, E. (Lithuanian Mathematical Journal, 1961)
The abstracts (in two languages) can be found in the pdf file of the article.Original author name(s) and title in Russian and Lithuanian:Э. Кирьяцкий. О функциях, n-я разделенная разность которых не равна нулюE. Kirjackis. Funkcijos, kurių n-tos eilės padalytas skirtumas nėra lygus nuliui